2013
DOI: 10.1093/nar/gkt001
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin mutations alter its nucleolar localization by impairing G-quadruplex binding at ribosomal DNA

Abstract: Nucleophosmin (NPM1) is an abundant nucleolar protein implicated in ribosome maturation and export, centrosome duplication and response to stress stimuli. NPM1 is the most frequently mutated gene in acute myeloid leukemia. Mutations at the C-terminal domain led to variant proteins that aberrantly and stably translocate to the cytoplasm. We have previously shown that NPM1 C-terminal domain binds with high affinity G-quadruplex DNA. Here, we investigate the structural determinants of NPM1 nucleolar localization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 44 publications
4
97
0
Order By: Relevance
“…29 Consistently with this picture, it was also shown that treatment of OCI-AML2 cells, bearing wild-type NPM1 at both alleles, with the G-quadruplex ligand TmPyP4 completely displaced NPM1 from nucleoli to the nucleoplasm. 34 Collectively, these data showed that a direct correlation exists between NPM1 C-terminal domain folding, G-quadruplex binding, and the nucleolar localization of the protein. Furthermore, as G-quadruplex regions are found at the nontemplate strand of the rDNA gene, 58 they will also be present in the pre-rRNA precursor, where they may be recognized by NPM1 C-terminal domain during prerRNA processing, even though this is still to be confirmed experimentally.…”
Section: G-quadruplex Binding and Nucleolar Localizationmentioning
confidence: 89%
See 4 more Smart Citations
“…29 Consistently with this picture, it was also shown that treatment of OCI-AML2 cells, bearing wild-type NPM1 at both alleles, with the G-quadruplex ligand TmPyP4 completely displaced NPM1 from nucleoli to the nucleoplasm. 34 Collectively, these data showed that a direct correlation exists between NPM1 C-terminal domain folding, G-quadruplex binding, and the nucleolar localization of the protein. Furthermore, as G-quadruplex regions are found at the nontemplate strand of the rDNA gene, 58 they will also be present in the pre-rRNA precursor, where they may be recognized by NPM1 C-terminal domain during prerRNA processing, even though this is still to be confirmed experimentally.…”
Section: G-quadruplex Binding and Nucleolar Localizationmentioning
confidence: 89%
“…Conversely, basespecific interactions and interactions with nucleotides belonging to the G-quadruplex connecting loops appear marginal, explaining why NPM1 recognizes with similar affinities several G-quadruplexes with varying loop structures. 34,45 As mentioned above, a lysine-rich region that flanks the terminal three-helix bundle (residues 225-242) proved necessary for high-affinity recognition of all oligonucleotides tested, despite their structure. 45 The overall positive charge of this tail seems to be important for recognition, as shown by the loss of G-quadruplex affinity displayed by a double lysine to alanine mutant (K229A-K230A) in the tail.…”
Section: Npm1 As a G-quadruplex-binding Proteinmentioning
confidence: 89%
See 3 more Smart Citations